Ministry of Trade And Industry Decree No. 149 of the Year 2023 On Rules and Procedures of Granting Temporary Operating Permits for the Unlicensed Industrial Institutions = وزارة التجارة والصناعة قرار رقم 149 لسنة 2023 بشأن قواعد وإجراءات منح تصاريح تشغيل مؤقتة للمنشآت الصناعية غير المرخص لها - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic